Promising technologies of grain storage during emergency situations - Barabolia, O.; Kyrychenko, D. (Scientific Progress & Innovations, 2022)
The analysis of the main technologies of grain storage was made in the article and their effectiveness considering the hostilities on the territory of Ukraine was determined. The current situation concerning granaries’ availability in Ukraine and their potential possibilities as to keeping grain of the new harvest were given. The necessity of developing innovative and effective technologies for grain products’ preservation because of the lack of granaries as well as attracting farmers to their use was mentioned. The main conditions for ensuring grain preservation in the optimal state on elevators were determined. The components of grain mass and factors of influence on it in order to determine the necessary storage conditions were characterized. The main grain keeping conditions (dry state, cooling, air-tightness) aimed at providing the integrity and quality of its reserves to use for any economic needs or selling during the following off-season were considered. The methods of grain keeping were given taking into account its further use – for processing or as seed material. The terms of grain storage depending on its condition and purpose were determined. The advantages and disadvantages of keeping technologies in stationary granaries considering the hostilities in Ukraine were analyzed: above-ground storage, concrete silo, metallic silo. It has been confirmed that at present the use of polymeric grain sleeves is one of the directions for making cheaper and substituting stationary granaries ruined during the hostilities. The characteristics of dry grain preservation technology in polymeric sleeves, its advantages and disadvantages under the present conditions were given. It has been mentioned that at the present stage such technology can be considered as the transitional one for the period of reconstruction and construction of stationary granary facilities.